Pengaruh Terapi Passion Flower (Passiflora Incarnata) terhadap Kualitas Tidur pada Remaja : The Impact of Passion Flower (Passiflora incarnata) Therapy on the Sleep Quality of Adolescents - Rahmawati, Novita Tsania; Herliana, Irma; Rizal, Ahmad (MPI Press, 2024)
Introduction: Sleep is an unconscious state that constitutes one of the basic human needs. Adequate sleep is determined by the amount of sleep (sleep quantity) and the depth of sleep (sleep quality). A lack of sleep can impact various aspects of a person's functioning, particularly memory and concentration. In this context, concentration refers to the ability to focus attention during learning activities. Objective: To determine the effect of passion flower tea on the sleep quality of adolescents at SMA/MA An-Najah, Bogor Regency, in 2022. Method: This study employed a quantitative approach with an experimental method. The research design used was pre-experimental, involving only one group as the experimental class along with a control group. The specific design was the one-group pretest-posttest with control group. Data were collected offline using a questionnaire. The test was conducted twice: before and after the intervention. The Wilcoxon test was used for data analysis. Results: The Wilcoxon test showed that sleep quality before and after the administration of passion flower tea had a significance value of 0.001, indicating a p-value < 0.05. According to the Wilcoxon test interpretation, if the p-value is less than 0.05, the hypothesis is accepted. Conclusion: Passion flower tea has a significant effect on improving sleep quality among adolescents at SMA/MA An-Najah, Bogor Regency, in 2022.